Evaluating the Use of Breast Self-Examination (BSE) for Recognizing Breast Cancer Awareness Among Jordanian Students and Workers in Medical Fields - Oglat AA; AbuKhalil T; Hasan H; Isawi IH; Oqlat AA; Abu Mhanna HY; Akhdar HF (Dove Medical Press, 2024)
Ammar A Oglat,1 Tala AbuKhalil,1 Hanan Hasan,2 Israa H Isawi,3 Ahmad A Oqlat,4 Hamad Yahia Abu Mhanna,5 Hanan Fawaz Akhdar6 1Department of Medical Imaging, Faculty of Applied Medical Sciences, The Hashemite University, Zarqa, Jordan; 2Department of Pathology, Microbiology and Forensic Medicine, School of Medicine, The University of Jordan, Amman, Jordan; 3Department of Medicinal Chemistry and Pharmacognosy, Faculty of Pharmacy, Jordan University of Science and Technology, Irbid, Jordan; 4Department of Accident and Emergency Medicine, Faculty of Medicine, Jordan University of Science and Technology, Irbid, Jordan; 5School of Physics, Universiti Sains Malaysia, USM, George Town, Penang, Malaysia; 6Physics Department, College of Science, Imam Mohammad Ibn Saud Islamic University (IMSIU), Riyadh, Saudi ArabiaCorrespondence: Ammar A Oglat, Email ammar.oglat@yahoo.comBackground: Globally, breast cancer (BC) is the most commonly detected neoplasm in women. Breast self-examination (BSE) is an effective screening technique that enables women to learn about the composition of their breasts and assist in the early identification of any potential breast abnormalities.Objective: This study aimed to assess the degree of BSE knowledge and attention among Jordanian females who are students or professionals in medical disciplines.Methods: Participants' knowledge about BSE and related issues was assessed using a self-administered questionnaire. The study invites participation from all females aged 18 and above, through both an online and in-person survey. The study extended invitations to female university students in Jordan across academic levels I, II, III, IV, V, and VI. A scoring system was employed, and the statistical analyses were performed using IBM SPSS Statistics (Version 20.0).Results: The study had 946 female participants, with 98.41% of them being single. Low BSE practice was reported among 90.49% of the participants (n = 856) and this demonstrated a weak understanding of BC disease, including its possible risks, methods of detection, diagnosis, treatment, signs and symptoms, as well as knowledge about mammography and other related information. Only 27.27% (n = 258) of participants practice BSE once a month and on a regular basis.Conclusion: BC is considered the most prevalent malignant condition and the second largest cause of cancer-related deaths for women in Jordan. Screening strategies are essential for promptly identifying breast cancer and reducing the associated illness and death rates. It is recommended that women commence performing BSE starting at the age of 18. Furthermore, it is essential to incorporate a learning outcome in the cancer chapters that are directly relevant to the subject of BC and emphasize the significance of BSE for students pursuing a career in the medical area. Keywords: breast cancer knowledge, self-examination, screening, Jordan